X=1
7*100=700
700=700/x => x=1
2) 4 ^ log4(8) = 8
(2^2)^log2^2(2^3)
(2^2)^(3/2)
2^3
8
3) log8(12) - log8(15) + log8(20) = 4/3
log8( (12*20) / 15 )
log2^3( (4*20) / 5)
log2^3( 4*4 )
log2^3( 2^4 )
4/3
1) (x²-4x)²-6(x-2)²=16;
(x²-4x)²-6(x²-4x+4)=16;
(x²-4x)²-6(x²-4x)-24-16=0.
Замена
x²-4x=t;
t²-6t-40=0
D=36+160=196
t=(6-14)/2=-4 или t=(6+14)/2=10
x²-4x=-4 или х²-4х=10
x²-4x+4=0 или х²-4х-10=0
D=16-16=0 D=16+40=56
x=2 x=(4-2√14)/2=2-√14 или х=2+√14
О т в е т. 2; 2-√14; 2+√14.
2) (33/(x²-6x+8))-x^2+6x=16.
(33/(x²-6x+8))-x²+6x-16=0.
(33/(x²-6x+8))-(x²-6x+16)=0.
Замена переменной
х²-6х+8=t t≠0
Уравнение примет вид:
(33/t)-(t+8)=0
-t²-8t+33=0
t≠-8
t²+8t-33=0
D=64+132=196
t=(-8-14)/2=-11 или t=(-8+14)/2=3
х²-6х+8=-11 или х²-6х+8=3
х²-6х+19=0 или х²-6х+5=0
D=36-76<0 D=36-20=16
не имеет корней х=(6-4)/2=-1 или х=(6+4)/2=5
О т в е т. х=-1; х=5
1 5/12 - 7/10 = 17/12 - 7/10 =<span> </span><span>(17 × 5 - 7 × 6)/60 = 85/60 - 42/60 = 43/60</span>